Exporting food, importing food aid? : Kenya and food security in the world food system - Esamwata, Joab O. (Kansas State University, 2014)
Food crises in Kenya are recurring phenomena. Despite widespread and perennial famines, Kenya is exporting food while importing food aid. This study focuses on the concept and question of food security in Kenya. If Kenya can produce and even export food products, why does the country still import food aid every year? Why is the country classified as food insecure? And why does the country still suffer from recurrent famines? Drawing on social science theory from the political economy of food and agriculture, this study postulates that the contradiction between exporting food and importing food aid is related to Kenya‟s subordinate position in the world economy. Using a comparative-historical, in-depth case study research design, this research descriptively explores the relationship between trends in food aid, trade, production and food security. The study finds that the relationship between food trade and aid with food security is mixed in Kenya. Aid and trade have not strongly enhanced food security in Kenya, but food insecurity in Kenya has not gotten markedly worse.
Keywords: Food security; World food system; Kenya; Sociology; Food Trade; Food aid; Sub-Saharan Africa Studies (0639)